2018
DOI: 10.1007/s11104-018-3594-9
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in red clover (Trifolium pratense L.) response under severe water deficit

Abstract: Aims In Ontario, Canada, acreage of red clover (Trifolium pratense L.) intercropped with winter wheat (Triticum aestivum L. em. Thell) has declined, despite well-documented soil and yield benefits. The decline has resulted from increasing prevalence of stand nonuniformity, which has been attributed in part to soil moisture deficits. We examined whether there are genotypic differences in drought response between red clover varieties. Methods A double-cut (Belle) and a single-cut variety (Altaswede) were grown u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…Red clover is one of the most common legume cover crops in southwestern Ontario, and the time of RC planting (late July to early August after wheat harvest) in this study has rarely been studied relative to the more conventional frost‐seeding (March to early April) (e.g., Vyn et al, 2000; Loucks et al, 2018). Coombs et al (2017) found less RC biomass accumulation in their study, in which RC was planted in late May to mid‐July relative to the RC planted in mid‐March to mid‐April in similar climates and they speculated that a shorter growing period could contribute to these results.…”
Section: Resultsmentioning
confidence: 99%
“…Red clover is one of the most common legume cover crops in southwestern Ontario, and the time of RC planting (late July to early August after wheat harvest) in this study has rarely been studied relative to the more conventional frost‐seeding (March to early April) (e.g., Vyn et al, 2000; Loucks et al, 2018). Coombs et al (2017) found less RC biomass accumulation in their study, in which RC was planted in late May to mid‐July relative to the RC planted in mid‐March to mid‐April in similar climates and they speculated that a shorter growing period could contribute to these results.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in winter canola, the crown tends to be raised in no tillage compared with conventional tillage (Assefa et al 2014). While this does not appear to affect canola winter survival, the ability of RC to survive summer moisture deficits could depend on conserving crown water content (Loucks et al 2018), which might be compromised if the crown is raised. Whether RC grows large enough in a WW stand to consider crown placement an issue is unclear.…”
Section: Id Quotesmentioning
confidence: 99%
“…Winter wheat (WW; Triticum aestivum L.) acreage in Ontario has increased 38.5% from 1941 to 2017; there were just over 370 000 ha of WW grown in 2017 (Hunt 1980;Kulasekera 2014;Mailvaganam 2018). At the same time, there has been a notable decline in wheat acreage being interseeded with red clover (RC; Trifolium pratense L.) in Ontario (Queen et al 2009;Gaudin et al 2013;Loucks et al 2018). Growers struggle to establish consistent RC stands following WW, and an increasing number are opting instead for other cover crops such as oat (Avena sativa L.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, early flowering has been shown to facilitate invasiveness (Pyšek and Richardson, 2008) and such a characteristic of the local germplasm can be accepted as validated by natural breeding to provide self-sowing and selfmaintenance of populations in the swards. Loucks et al (2018) suggest that under conditions of water stress, red clover populations with different growth habit have different strategies of tolerance or survival. The observed change in the growth habit of local populations by cuts can be explained as a modifiable variability in response to changing climatic conditions in seasons.…”
Section: Discussionmentioning
confidence: 99%